Biochemical Assessment of Selected Nutrients Among Alcohol-Dependent Males Before and After Rehabilitation at Mathari National Teaching and Referral Hospital, Kenya - LANGAT, Emmy CHERONO; CHRISTINE ONYANGO, Agatha; KIPROTICH, Chelimo (African Journal of Nutrition and Dietetics, 2025)
Kenya faces numerous public health challenges, including alcohol abuse. Studies show that alcohol and drug abuse can disrupt nutrition, contributing to preventable diseases and deaths. Although nutrient deficiencies in alcoholism may be managed through nutrition therapy, the role of nutrition rehabilitation in Kenya remains underexplored. This study assessed the biochemical nutritional status of Albumin, Calcium, Magnesium, and Zinc among alcohol-dependent patients before and after rehabilitation. A pre–post experimental design was used among 62 consecutively sampled patients, assessed on admission and after 90 days. Data were collected using semi-structured questionnaires, and blood samples were analyzed for nutrient biomarkers and compared with reference standards. Nutrient adequacy proportions and mean levels before and after rehabilitation were compared using Chi-square and T-tests. Mean serum calcium increased significantly (t=2.428, P=0.018), while serum albumin and zinc showed slight, non-significant increases (t=0.742, P=0.461; t=0.445, P=0.658). Serum magnesium declined slightly (t=0.912, P=0.36). A significant increase in the number of patients with adequate nutrient levels was observed for albumin (χ2=7.3518, P=0.0067), magnesium (χ2=91.782, P=0.001), and zinc (χ2=8.1986, P=0.0042). Post-rehabilitation adequacy improved notably: albumin from 32.4% to 56.8%, zinc from 21.6% to 45.9%, and magnesium from 13.5% to 100%. Rehabilitation was associated with improved nutrient levels and biochemical adequacy among patients, highlighting its role in recovery. Based on these findings, comprehensive nutrition care should be integrated into alcohol rehabilitation programs. The government and program managers should consider developing and implementing a national alcohol and nutrition rehabilitation policy to support recovery outcomes.